ChemInform Abstract: Chemical Constituents from Nelumbo nucifera Leaves and Their anti‐Obesity Effects. Issue 40 (12th September 2013) - Ahn, Jong Hoon; Kim, Eun Sil; Lee, Chul; Kim, Soonok; Cho, Soo‐Hyun; Hwang, Bang Yeon; Lee, Mi Kyeong
Abstract isolation, structure determination and biological activities of 33 constituents including the new megastigmane, nelumnucifoside A (I), and the new eudesmane sesquiterpene, nelumnucifoside B (II)